PENERAPAN PERMAINAN KECIL BOLA BERACUN PADA PEMBELAJARAN PJOK UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS 10 DI SMAN 1 KEJAYAN - Wafiq Roisul Umami; Irawan Firmansyah; Putranto Ari Muhammad; Taufiq Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The research activity was motivated by the phenomenon during PJOK learning activities which showed low learning motivation in students in class 10 of SMA Negeri 1 Kejayan. The research was carried out with the aim of obtaining data and information regarding increasing students' learning motivation in the form of implementing a small poison ball game in PJOK learning. The type of research chosen to obtain learning motivation results is classroom action research, which is structured and sequential, namely, first the planning activity procedure, second the implementation activity, third the observation activity and fourth the reflection activity. The population in the research were 10th grade students at SMA Negeri 1 Kejayan with a total of 36 students. The research time was carried out for around two months and questionnaire filling activities were carried out in two cycles and data collection activities on student learning motivation were carried out through motivation questionnaires and interviews and then analysis was carried out. using descriptive quantitative methods. The research results showed that there was an increase in learning motivation among students from cycle 1 to cycle 2 in the form of filling out motivation questionnaires in PJOK learning